GAMBARAN DERAJAT BERAT MEROKOK BERDASARKAN KADAR CO PADA PEROKOK DI POLI PARU RSUD ARIFIN ACHMAD PROVINSI RIAU - Ayu Warma; Sri Melati Munir; Eka Bebasari (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTCigarette is the result of tobacco processed which contains dangerous chemical materials. When cigarette burned it will be produced the carbon monoxide gases. If the CO gases inhaled that gas will makes a binding with Hb become HbCO. The CO concentration in blood will be balance with the CO level expire air. micro CO meter is effective to evaluate the CO level in expiration air . So it can be determined the degree of heavy smoking . Besides using the micro CO meter the heavy degree of smoking can also determined by Brinkman Index. This research used an observational study using descriptive crossectional design. This sampling used accidental sampling methods with 97 samples. This study showed that active smokers in pulmonary polyclinic of Riau Province General Hospital Arifin Achmad with the age group with commonly characteristic at 44-54 year old 26 persons (26,80%), highest sex group was male with 94 respondence (96,91%), daily consumption of cigarettes for more than 20 pieces are 40 people (41,24%), 39 people (40,21%) have their smoking period for >20 years and most types of cigarette are kretek 81 people (83,51%). According to Brinkman Indeks, smoking level was on the medium smoker degree with 41 patuents (42,27%) while micro CO meter showed heavy smoker degree with 63 patients (64.95%).Keywords : cigarette, CO, Brinkman Index, micro CO meter